Sophie's dilemma eaudiobook Daughters of blessing series, book 2. - Snelling, Lauraine (Daughters of Blessing,, 2008)
Award-winning historical novelist Lauraine Snelling delivers a compelling sequel to A Promise for Ellie. When 17-year-old Sophie abandons her North Dakota family in 1901, she never dreams tragedy will turn her again toward home. But she fears the loved ones she hurt will reject her-and that she'll never love again. ". a fantastic tale of love, loss, and second chances."-Romantic Times